Chronic cough in Germany: results from a general-population survey. Issue 1 (10th January 2022) - Virchow, J. Christian; Li, Vicky W.; Fonseca, Eileen; Salmen, Helena; Martin, Ashley; Brady, Joanne; Jannowitz, Christina; Schelfhout, Jonathan
Background: Chronic cough (CC) which is defined ≥8 weeks is a common condition in clinical practice. However, estimates of prevalence and associated comorbidities in German adults and key subgroups of age and gender are lacking. Methods: Cross-sectional study based on a representative panel of 15 020 adult subjects of the general population who completed the German National Health and Wellness Survey, reporting CC and questions about comorbidities. Lifetime and 12-month prevalence are presented as unweighted estimates. Results: The lifetime CC prevalence was 6.5% (range across age groups 5.1%–8.3%) and the 12-month prevalence was 4.9% (range 3.7–5.7%). The prevalence of diagnosed CC was 2.8% (range 0.9–4.1%) and the prevalence of persons currently on any prescription to treat CC was 0.6% (range 0.2–1.4%). Respondents who experienced CC were 52.0±17.0 years old, with a higher prevalence in those aged 50 years and older. Persons with CC had higher morbidity scores and were diagnosed with an increased number of comorbidities, most frequently diagnoses of the respiratory system (71.0%), followed by digestive tract disorders (34.0%) and sleep disorders (37.6%). Conclusions: In a broadly representative sample of German adults, lifetime and 12-month prevalence of CC was greatest in current and former smokers and those older ≥50 years of age. Comorbidities are frequent and may complicate management of these patients. Chronic cough is a prevalent condition in Germany among all age groups, regardless of sex, with highest rates in those 18–29 and ≥50 years, and more frequent among current or prior smokers. Comorbidities are common in this population. https://bit.ly/3uiYj4w